Presentations and management of different causes of chylothorax in children: one medical center’s experience - Lin Chien-Heng; Lin Wei-Ching; Chang Jeng-Sheng (BioMedicine, 2017)
Background: Chylothorax in children is a relatively rare cause of pleural effusion. However, it is usually a common complication of cardiothoracic operations like open-heart surgery. Other etiologies for chylothorax, such as trauma or malignancy, occur more common in adults and rare in children. To explore the etiologies of chylothorax in children, this study analyzed the pediatric patients that were admitted in to onea medical center. Methods: We retrospectively reviewed the medical records of the pediatric patients that were admitted to this tertiary transfer center with a diagnosis of chylothorax during the period of 1995 to 2005. Results: A total of 22 patients (15 females and 7 males) with chylothorax were enrolled in our study. The etiologies for chylothorax were the following: a complication of cardiothoracic surgery in 14 patients (63.6%), congenital chylothorax in 5 patients (22.7%), association with neuroblastoma in 2 patients (9.1%), and congenital nephrotic syndrome in 1 patient (4.6%). All patients required medical therapy. Chest tube drainage was necessary to provide for twenty patients (90.9%), and surgical intervention was necessary to perform for 3 patients (13.6%). Four patients (18.2%) expired due to other causes. Conclusion: Cardiothoracic surgery was the most common cause of chylothorax in children at the institution surveyed. Medication and chest tube drainage were effective in treating most of these chylothorax-afflicted patients. In addition, early recognition, medication, and performing surgical intervention when necessary are important measures to avoid a catastrophe.